Forgone injury treatment among young adult skateboarders - Ravert, R. D.; Oberfranc, K. J.; Dannecker, E. A. (Journal of Human Sport & Exercise, 2023)
Adolescents and young adults have high levels of forgone healthcare relative to other age groups, placing those who participate in action sports at particularly high risk for untreated injuries. Because skateboard injury data typically involves treated injuries, research to understand unmet health needs in non-clinical samples is needed. This exploratory study used qualitative content analysis of survey and structured interviews with young adult skateboarders (n = 26, mean age = 22.9 years) recruited at skate parks in a small U.S. city to examine the degree, type, and reported reasons for untreated skateboard injuries in that population. Participants completed a paper survey followed by a structured interview regarding their untreated skateboard injuries and reasons for avoiding medical treatment. A majority of respondents (80.8%) described at least one skateboarding injury that they did not have medically treated but now believe they should have done so. Injury types were deep soft tissue injuries (50.0% of respondents), bone fractures (15.4%), concussions (11.5%), and superficial soft tissue injuries (3.8%). Of respondents who avoided treatment, 76.2% considered treatment unnecessary at the time, 38.1% cited avoiding treatment due to cost, and 23.8% cited lack of knowledge. Findings suggest a need to address forgone injury care among young adult skateboarders through increased support and knowledge regarding when and how to seek affordable medical treatment.